Promoting optoelectronic properties of Cs2AgBiBr6 nanocrystals by formation of heterostructures with BiOCl nanosheets. Issue 56 (22nd June 2022) - Yang, Lei; Li, Yuping; Zhang, Wei; Liu, Yanlei; Cao, Jiacheng; Cao, Yang; Bao, Jusheng; Wang, Zhiwei; Wang, Lin; Huang, Xiao
Abstract : The photoluminescent and photodetection properties of lead-free double perovskite Cs2 AgBiBr6 nanocrystals were enhanced upon formation of heterostructures with BiOCl nanosheets through a colloidal synthesis method. Abstract : Lead halide perovskite nanocrystals and their heterostructures have achieved substantial advances in optoelectronics; however, their inherent material instability and lead toxicity have driven research on alternative material systems. Herein, solution-processable heterostructures composed of lead-free double perovskite Cs2 AgBiBr6 nanocrystals and BiOCl nanosheets were prepared through a colloidal synthesis method. Defect states were present in BiOCl and benefited carrier generation, recombination and transport in Cs2 AgBiBr6 . As a result, the light emission of the Cs2 AgBiBr6 nanocrystals was greatly enhanced at low temperatures, and the photodetector based on the Cs2 AgBiBr6 /BiOCl heterostructure exhibited a much improved on-off ratio compared to the device based on Cs2 AgBiBr6 alone. Our work highlights the complex nature and impact of two-dimensional heterostructure assembly on the optoelectronic properties of lead-free double perovskites and demonstrates their great potential toward environmentally friendly optoelectronic devices.